The Influence of Motivation and Leadership Style on Employee Performance of Regional Financial and Asset Agencies - Aris, Lukas; Mujahid, Mujahid; Bidol, Syamsuddin (Newinera Publisher, 2023)
The study aims to identify and analyze the influence of motivation and leadership style on the performance of officials at the Office of the Regional Financial and Asset Authority of Paniai District of Central Papua Province. The research was conducted in the office of the Paniai district financial and asset agency located on the Kaisepo street in the Eastern Pania district. The sample in this study is a total of 45 civil servants. Research findings show that motivation influences staff performance, leadership style influences employee performance and simultaneously motivation and leadership styles influence staff performance at the financial and asset offices of the district of Panya Province of central Papua.